IMPLEMENTATION OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) METHOD TO IMPROVE LEARNING QUALITY IN CLASS V ELEMENTARY SCHOOL - Saripah, Saripah; Rosmaladewi, Okke (Jurnal Konseling Pendidikan Islam, 2025)
This study stems from the low learning motivation observed among fifth-grade students, particularly in the Natural and Social Sciences (IPAS) subject, which is often perceived as complex. Contributing factors include limited variation in teaching methods, monotonous instructional media, and abstract material delivery. These issues manifest in low student engagement and learning outcomes falling below the Minimum Completion Criteria (KKM). The research aims to enhance student motivation and learning outcomes through the application of the Contextual Teaching and Learning (CTL) approach in IPAS lessons at SDN Munjul (Cilaku District) and SDN Sukmajaya (Cugenang District), Cianjur Regency. Employing a descriptive qualitative method with a case study design, the research follows the PDCA (Plan, Do, Check, Action) cycle. Data were collected via observation, in-depth interviews, documentation, and learning outcome tests, involving principals, teachers, and students. Analysis used the Miles and Huberman interactive model: data reduction, presentation, and conclusion drawing. The study focused on fifth-grade students from both schools. Findings reveal that CTL significantly boosts student motivation and participation, as well as improves learning outcomes—most students achieved or exceeded the KKM. In conclusion, the CTL method proves to be an effective, meaningful, and contextually relevant pedagogical approach for enhancing IPAS learning quality at the elementary level.